Unimodal rays in the ordinary and generalized pascal triangles - Belbachir H (JOURNAL OF INTEGER SEQUENCES - ONLINE, 2008)
The present paper provides the solution of two problems recently posed by Bencherif, Belbachir and Szalay. For example, they conjectured that any sequence of binomial coefficients lying along a ray in Pascal's triangle is unimodal.